WaveformECG: A Platform for Visualizing, Annotating, and Analyzing ECG Data - Winslow, Raimond L.; Granite, Stephen; Jurado, Christian (Computing in science & engineering, 2016)
The electrocardiogram (ECG) is the most commonly collected data in cardiovascular research because of the ease with which it can be measured and the fact that changes in ECG waveforms reflect underlying aspects of heart disease. Despite its ubiquity, there are no open, noncommercial platforms for interactive management, sharing, and analysis of these data. WaveformECG addresses this unmet need. Accessed through a browser, WaveformECG extracts ECGs from vendor files, storing them as a time series with other analysis results and annotations in an open source time-series database. It supports interactive invocation of multiple analysis algorithms on selected ECG datasets, visualization of ECG waveforms, manual annotation of time points and intervals in ECG waveforms, and automated annotation of analysis results using standard medical terminology. Integration with the I2B2 clinical data warehouse system enables bidirectional exchange of data between these two platforms.